Bringing Financial Literacy and Education to Low and Middle Income Countries : The Need to Review, Adjust, and Extend Current Wisdom - Holzmann, Robert (World Bank, Washington, DC, 2017)
This paper presents a World Bank led and Russia trust fund financed work program to measure financial capability and the effectiveness of financial education in low and middle income countries. The two activities and their staging have been motivated by the lessons of high income countries with financial literacy programs and the deviating characteristics of low and middle income countries. While progress has been made in high-income countries to measure financial capability, there is little robust empirical evidence that financial education can improve it. While applying the financial capability concept in low and middle-income countries looks promising it will need to be adjusted to their characteristic and supported by innovative interventions and rigorous impact evaluation to improve it.